1997
DOI: 10.1128/iai.65.6.2278-2282.1997
|View full text |Cite
|
Sign up to set email alerts
|

Depletion of alveolar macrophages exacerbates respiratory mycoplasmosis in mycoplasma-resistant C57BL mice but not mycoplasma-susceptible C3H mice

Abstract: Indirect evidence suggests that innate immune mechanisms involving alveolar macrophages (AMs) are of major importance in antimycoplasmal defense. We compared the effects of AM depletion on intrapulmonary killing of Mycoplasma pulmonis during the early phase of infection in mycoplasma-resistant C57BL/6NCr (C57BL) and mycoplasma-susceptible C3H/HeNCr (C3H) mice. More than 80% of AMs were depleted in both strains of mice by intratracheal insufflation of liposome-encapsulated dichloromethylene bisphosphonate (L-Cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(19 citation statements)
references
References 35 publications
(52 reference statements)
1
18
0
Order By: Relevance
“…Although we found that a distinct BAL cytokine and chemokine profile correlated with pulmonary function abnormalities when comparing M. pneumoniae infection in BALB/c mice and C57BL/6 mice, it is also known that other immunologic and genetic differences exist between these mouse strains, which could affect experimental outcomes. These differences include innate immunity (alveolar macrophages), mast cell tryptase, IL-9, total and specific IgE, and dendritic cell subsets (49)(50)(51). Furthermore, these two mouse strains have genetic differences in the H-2 region (murine major histocompatibility complex) and in other H-2-associated genes, mimicking the differences in major histocompatibility complex among humans (24,29,30).…”
Section: Discussionmentioning
confidence: 99%
“…Although we found that a distinct BAL cytokine and chemokine profile correlated with pulmonary function abnormalities when comparing M. pneumoniae infection in BALB/c mice and C57BL/6 mice, it is also known that other immunologic and genetic differences exist between these mouse strains, which could affect experimental outcomes. These differences include innate immunity (alveolar macrophages), mast cell tryptase, IL-9, total and specific IgE, and dendritic cell subsets (49)(50)(51). Furthermore, these two mouse strains have genetic differences in the H-2 region (murine major histocompatibility complex) and in other H-2-associated genes, mimicking the differences in major histocompatibility complex among humans (24,29,30).…”
Section: Discussionmentioning
confidence: 99%
“…Despite these multiple interactions, the organisms seem to be relatively resistant to phagocytosis in susceptible hosts and to replicate on the surface of phagocytic cells, unless opsonized by specific antibodies (91,93,189) or complement components (281). In fact, it has been shown that at early stages of infection, the ability of alveolar macrophages to kill M. pulmonis differed among various mouse strains and thereby controlled their susceptibility or resistance to infection (179). Moreover, in vitro studies with M. pulmonis, peritoneal macrophages, and lymphocytes obtained from a susceptible mouse strain showed that the cytokines produced during mitogenic stimulation of the lymphocytes did not increase the phagocytic properties of macrophages toward M. pulmonis (91).…”
Section: Activation Of Immune Cells By Mitogenic Mycoplasmasmentioning
confidence: 99%
“…Down-regulation of acute respiratory tract inflammatory responses may occur when cytokines such as IL-10 (336) or IFN-␣ (307), together with soluble cytokine receptors (200,437) or possibly with other downregulating, anti-inflammatory cytokines such as IL-4, TGF-␤, and IL-13 or cytokine antagonists, accumulate and exert their anti-inflammatory effects. Differential killing of invading organisms by alveolar macrophages from various hosts (179,281), differences in the capacity of various Mycoplasma strains to induce the production of cytokines by monocytes (209) and to polyclonally stimulate lymphocytes (309,420), and variation in the potentials of different host strains and species to mount an inflammatory response (122) may have a major impact on the resulting virulence of mycoplasmas infecting the respiratory organs and on disease manifestation in different hosts.…”
Section: Activation Of Immune Cells By Mitogenic Mycoplasmasmentioning
confidence: 99%
“…Although Ctsl-null mice mounted robust humoral responses to mycoplasma antigen, the inability of splenocytes from infected Ctsl 2/2 mice to produce IFN-g in response to mycoplasma antigen suggests a possible defect in cell-mediated immune responses (38). In the context of M. pulmonis infection, in which activated macrophages are thought to play an important and possibly critical role in controlling infection (13,16,39), a deficit of the antigen-stimulated production of IFN-g, which is a macrophageactivation factor (38), could blunt macrophage responses to mycoplasma. Our experiments predict that Ctsl inhibitors could have the unintended consequence of increasing the severity of respiratory mycoplasmal infection, a possibility that should be assessed in developing and applying Ctsl inhibitors to a clinical context.…”
mentioning
confidence: 99%